Deduction of full factorial design of HPLC technique for the simultaneous analysis of meloxicam and esomeprazole in their laboratory prepared tablets - Hesham Sameh Ramadan; Fathalla Belal; Aya Roshdy; Mohamed M. Salim (Scientific Reports)
Abstract A reversed phase HPLC method with UV detection was designed for the first time for the simultaneous estimation of meloxicam and esomeprazole in their combined tablet dosage forms. Full factorial design was used for rapid optimization of the proposed method. Chromatographic separation was reached using isocratic elution on C18 column. The mobile phase was a mixture of methanol: acetonitrile: 0.05 M potassium dihydrogen phosphate buffer at pH 5, adjusted using phosphoric acid and/or NaOH when needed. The flow rate was 1 mL/min and the injection volume was 20 µL. The detection wavelength was 230 nm. The working ranges of the method were 5.0-100.0 and 10.0–100.0 µg/mL, LOD values were 0.8 and 1.8 µg/mL and LOQ values were 2.6 and 5.5 µg/mL for meloxicam and esomeprazole, respectively. The proposed method was successfully applied to their combined tablet dosage forms with acceptable % recoveries (100.4 − 100.7%) obtained. Four methods were used to evaluate the greenness of the proposed method, suggesting the acceptability of the greenness of the proposed method.